Promoting tourism destinations through Sudanese tourists interacting experiences in Bandung - Musa, Hussein Gibreel; Mulyana, Deddy; Bajari, Atwar; Navarro, Charles Julian Santos (Faculty of Communications Science, Dr. Soetomo University, 2020)
the research focus about tourism because it’s among the most widely used commonly discussed to promising economic sector, which varies from one country to another specially in developing countries its became main resources to some countries. Today, these countries are opening up new marketing tool to promote their destinations, Suitable distribution and intensive promotion, which will increase the period of residence of the tourist and increase the national income by relying on a promotional strategies in social media based on tourists experiences. Indicating the gap in knowledge and possible limitations the researcher used the qualitative approach in this study; because the research focused on how the developing countries, especially Indonesia benefit from the social media as new marketing tool in promoting destinations, also studying the topic as a new phenomenon in Indonesia, because most of Sudanese tourists are using social media to find information about tourism destinations in Indonesia. The researcher conducted a short interview with six Sudanese tourists to understand the Sudanese tourists' behavior, communication experiences in social media, and the factors (pull and push factors) that make the Sudanese tourists' decide to choose Indonesia. The result showed that most of the Sudanese tourists are using social media to share their travel experiences in destination by posting pictures, videos, even comments and opinions. These postings had serve as valuable information for other potential tourists and has influenced their choices.